Risk of infection associated with intravenous iron preparations: protocol for updating a systematic review. Issue 6 (4th June 2019) - Shah, Akshay; Sugavanam, Anita; Reid, Jack; Palmer, Antony J; Dickson, Edward; Brunskill, Susan; Doree, Carolyn; Oliver, Charles M; Acheson, Austin; Baikady, Ravi Rao; Bampoe, Sohail; Litton, Edward; et al.
Abstract : Introduction: The benefits and risk of intravenous iron have been documented in previous systematic reviews and continue to be the subject of randomised controlled trials (RCTs). An ongoing issue that continues to be raised is the relationship between administering iron and developing infection. This is supported by biological plausibility from animal models. We propose an update of a previously published systematic review and meta-analysis with the primary focus being infection. Methods and analysis: We will include RCTs and non-randomised studies (NRS) in this review update. We will search the relevant electronic databases. Two reviewers will independently extract data. Risk of bias for RCTs and NRS will be assessed using the relevant tools recommended by The Cochrane Collaboration. Data extracted from RCTs and NRS will be analysed and reported separately. Pooled data from RCTs will be analysed using a random effects model. We will also conduct subgroup analyses to identify any patient populations that may be at increased risk of developing infection. We will provide a narrative synthesis on the definitions, sources and responsible pathogens for infection in the included studies. Overall quality of evidence on the safety outcomes of mortality and infection will be assessed using the Grading of Recommendations, Assessment, Development and Evaluation approach. Ethics and dissemination: This systematic review will only investigate published studies and therefore ethical approval is not required. The results will be broadly distributed through conference presentations and peer-reviewed publications. Trial registration number: PROSPERO (CRD42018096023 ).